2020
DOI: 10.1111/sum.12657
|View full text |Cite
|
Sign up to set email alerts
|

Determining Mehlich‐3 and DTPA extractable soil zinc optimum economic threshold for maize

Abstract: Zinc (Zn) deficiency is the most widespread micronutrient deficiency in crops, and it affects more than 160 million ha of arable land worldwide (Alloway, 2009). Maize (Zea mays L.) is one of the most susceptible crops to this nutrient deficiency (Brown et al., 1993). Zinc deficiency can be avoided by the application of Zn fertilizers. However, to achieve rational Zn fertilizer management, the development, correlation, calibration and interpretation of soil test methods to diagnose plant-available soil Zn are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
2
3
0
Order By: Relevance
“…In soils from the Pampas region, Barbieri et al (2017) andMartínez Cuesta et al (2020) reported DTPA-Zn critical thresholds for corn (0.99 and 1.02 mg kg −1 , respectively) similar to the one determined for wheat in the present study. Although corn has a greater potential yield than wheat, and thus a greater absolute demand for Zn per unit area, both crops have similar aboveground Zn requirement for grain production (∼42-55 g Zn Mg −1 ) (Nayyar et al, 2001;Bender et al, 2013;Ciampitti & Vyn et al, 2013;Liu et al, 2019).…”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…In soils from the Pampas region, Barbieri et al (2017) andMartínez Cuesta et al (2020) reported DTPA-Zn critical thresholds for corn (0.99 and 1.02 mg kg −1 , respectively) similar to the one determined for wheat in the present study. Although corn has a greater potential yield than wheat, and thus a greater absolute demand for Zn per unit area, both crops have similar aboveground Zn requirement for grain production (∼42-55 g Zn Mg −1 ) (Nayyar et al, 2001;Bender et al, 2013;Ciampitti & Vyn et al, 2013;Liu et al, 2019).…”
Section: Resultssupporting
confidence: 85%
“…Also, wheat GY response to Zn fertilization and RY were not correlated with the maximum yield at each site (p = .54 and p = .62, respectively). This behavior has already been reported for Zn in corn (Barbieri et al, 2017;Martínez Cuesta et al, 2020) and other nutrients with low soil mobility (Dodd & Mallarino, 2005) that reach the root surface by diffusion and root interception (Bray, 1954). These observations suggest that the GY response to Zn fertilization is more related to the capacity of soils to provide available Zn to the roots than to the absolute crop demand for Zn.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…EDTA and DTPA are two chelating agents commonly used in sorption-desorption studies due to their ability to form stable complexes with a wide variety of metals. The nonselective nature of EDTA in metal extraction is a disadvantage, as this agent extracts a wide variety of metals, including alkaline earth cations such as Ca and Mg. Another disadvantage would be that EDTA is hardly biodegradable and can remain adsorbed on soil particles [34,35]. With calcium being the primary cation of the adsorption complex of soils, the M2-CaCl 2 solution is more capable of extracting other cations adsorbed on the surface of soil particles than other solutions without Ca.…”
Section: Evaluation Of the Influence Of Factors On The Extraction Of ...mentioning
confidence: 99%